Kalosi Shop Business Strategy in the Post-Covid-19 Pandemic Era - Imaduddin Imaduddin (Newinera Publisher, 2023)
This research was conducted to reveal matters related to the Kalosi shop business strategy in the post-pandemic era. This research uses descriptive qualitative methods. The subject of the research is the founder/owner of the Kalosi shop business. Using interview, observation and documentation data collection methods, we can dig deeper into the findings. Data analysis consists of data collection, data reduction, data presentation, explaining categories and verifying findings. The results of the research reveal that factors related to the Kalosi shop business strategy include product quality, price, customer loyalty, strategic location, available facilities, innovativeness, hard working attitude, good communication with consumers, good news (word of mouth information).